Disparities in access to anti‐vascular endothelial growth factor treatment for neovascular age‐related macular degeneration. (12th September 2016) - Finger, Robert P; Xie, Jing; Fotis, Kathy; Parikh, Sumit; Cummins, Rob; Mitchell, Paul; Guymer, Robyn H
Abstract: Background: Late neovascular age‐related macular degeneration (nvAMD) is very common and causes irreversible severe visual loss unless treated swiftly with vascular endothelial growth factor (VEGF) inhibitors. Although publicly subsidized access to treatment may be inequitable, which is why we assessed treatment provision across Australia. Design: Secondary analysis of Australian data. Participants: All Pharmaceutical Benefits Scheme (including Repatriation PBS) beneficiaries. Methods: Treatment and incidence data were obtained from Medicare Australia, the Royal Australian and New Zealand College of Ophthalmologists, Optometry Australia, the Blue Mountains Eye Study and the Australian Bureau of Statistics. Data were mapped using geographical information software, and factors associated with treatment provision were assessed using multiple linear regression models. Main Outcome Measure: Unmet need (%) for anti‐VEGF treatment for nvAMD. Results: On average, we estimated 7316 incident cases of nvAMD not to be treated per year from 2010 to 2014 (50.1% of total). Number of ophthalmologists and optometrists (per 1000, β = −0.024; 95% confidence interval [CI] −0.041, −0.007) and being located in remote regions (β = 0.186; 95% CI 0.110, 0.262) were associated with percentage of untreated cases. A higher proportion of the population speaking a language other than English at home was associated in univariate analyses only (β = 0.0015; 95% CI −0.0004, 0.0027; P = 0.007). Conclusion: A large proportion of incident nvAMD is not treated with anti‐VEGF. Not receiving treatment is more likely in regional or remote areas and areas with fewer service providers. Not speaking English at home may further limit access. Service delivery models for more equitable service provision are needed.